2014
DOI: 10.1063/1.4880276
|View full text |Cite
|
Sign up to set email alerts
|

Model for triplet state engineering in organic light emitting diodes

Abstract: Engineering the position of the lowest triplet state (T1) relative to the first excited singlet state (S1) is of great importance in improving the efficiencies of organic light emitting diodes and organic photovoltaic cells. We have carried out model exact calculations of substituted polyene chains to understand the factors that affect the energy gap between S1 and T1. The factors studied are backbone dimerisation, different donor-acceptor substitutions, and twisted geometry. The largest system studied is an 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Identification of various nonradiative decay pathways arising from vibronic coupling effects in the dense excited triplet manifold is quite a challenging task. Nevertheless, detailed investigations of such decay pathways could provide important insights into basic aspects of singlet fission, , triplet–triplet annihilation, , and reverse intersystem crossing processes. …”
Section: Jahn–teller Effectsmentioning
confidence: 99%
“…Identification of various nonradiative decay pathways arising from vibronic coupling effects in the dense excited triplet manifold is quite a challenging task. Nevertheless, detailed investigations of such decay pathways could provide important insights into basic aspects of singlet fission, , triplet–triplet annihilation, , and reverse intersystem crossing processes. …”
Section: Jahn–teller Effectsmentioning
confidence: 99%
“…610 In recent times, theoretical and computational investigations have also predicted some conjugated systems with small S 1 –T 1 energy gaps. 1114 In those cases, the S 1 –T 1 energy gap has been calculated using time-dependent density functional theory (TDDFT), single configuration interaction (SCI), and the full CI technique. Gierschner et al reported carbozole–paraterphenyl systems with donor–acceptor (D–A) substituents.…”
Section: Introductionmentioning
confidence: 99%
“…In general, for conjugated systems, the lowest triplet energy E (T 1 ) is lower than the lowest singlet energy E (S 1 ), however in the process of RISC, it is very desirable to have a S 1 –T 1 energy gap that is of the order of k B T (0.025 eV) so that S 1 can be populated thermally. There are some experimental reports on such conjugated systems with very small S 1 –T 1 energy gaps (0.04 eV). In recent times, theoretical and computational investigations have also predicted some conjugated systems with small S 1 –T 1 energy gaps. In those cases, the S 1 –T 1 energy gap has been calculated using time-dependent density functional theory (TDDFT), single configuration interaction (SCI), and the full CI technique. Gierschner et al reported carbozole–paraterphenyl systems with donor–acceptor (D–A) substituents .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations